2014
DOI: 10.1007/s00125-014-3352-3
|View full text |Cite
|
Sign up to set email alerts
|

The coactivator PGC-1α regulates skeletal muscle oxidative metabolism independently of the nuclear receptor PPARβ/δ in sedentary mice fed a regular chow diet

Abstract: Aims/hypothesis-Physical activity improves oxidative capacity and exerts therapeutic beneficial effects, particularly in the context of metabolic diseases. The peroxisome proliferatoractivated receptor γ (PPARγ) coactivator-1α (PGC-1α) and the nuclear receptor PPARβ/δ have both been independently discovered to play a pivotal role in the regulation of oxidative metabolism in skeletal muscle, though their interdependence remain unclear. Hence, our aim was to determine the functional interaction between these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…In our study, we found significantly increased expression of PPARD after a training cycle of 2 months. Our results are consistent with other authors’ results of research on animals models [ 30 , 31 , 32 ]. Mice undergoing endurance exercise showed an accumulation of PPARβ/δ protein in muscle [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, we found significantly increased expression of PPARD after a training cycle of 2 months. Our results are consistent with other authors’ results of research on animals models [ 30 , 31 , 32 ]. Mice undergoing endurance exercise showed an accumulation of PPARβ/δ protein in muscle [ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The skeletal muscle is an organ that plays a key role in such processes ( 26 ). One of the best-described cofactors of PPARδ is a transcriptional coactivator ( 27 ). Targeting of PPARδ with miR-29a suggests that this miRNA contributes to the regulation of the corresponding metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Energy metabolism in skeletal muscle is regulated by PPARγ coactivator-1α (PGC-1α), a regulator of mitochondrial biogenesis [ 28 ], involved in the catabolic process to synthesize aerobic adenosine triphosphate (ATP). PGC-1α expression is directly activated by PPARβ/δ to regulate skeletal muscle metabolism by increasing the expression of mitochondrial proteins [ 29 , 30 ]. PGC-1α stimulates the expression of genes responsible for glucose and lipid metabolism, energy transfer, and muscle contractile function.…”
Section: Ppar Signals In Skeletal Musclementioning
confidence: 99%